2020
DOI: 10.3390/microorganisms8060879
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Microbiome of Cryptosporidium-Infected Mice Correlate to Differences in Susceptibility and Infection Levels

Abstract: Cryptosporidium spp. are opportunistic protozoan parasites that infect epithelial cells of the small intestine, causing diarrheal illness in humans. Differences in severity may be due to the immunological status of the host, malnutrition or prior exposure but may also be due to differences in the host gut flora. We examined changes in bacterial flora following antibiotic treatment to determine how cryptosporidial infections and gut integrity were affected by alterations in the microbiome. DNA was extracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
1
30
1
Order By: Relevance
“…Individuals infected with Entamoeba histolytica , the causative agent of amebiasis, were found to have a decreased abundance of protective bacteria generally associated with gut health ( Verma et al, 2012 ). Cryptosporidium was found to alter microbiota composition in mouse models as well as in primates (Coquerel’s sifakas – Propithecus coquerel ), and dysbiosis was associated with enhanced parasite growth ( Ras et al, 2015 ; McKenney et al, 2017 ; Charania et al, 2020 ). Individuals infected with the protist Blastocystis show increased diversity of the gut microbiota in their fecal contents ( Audebert et al, 2016 ; Nieves-Ramirez et al, 2018 ).…”
Section: The Intestinal Microbiomementioning
confidence: 99%
“…Individuals infected with Entamoeba histolytica , the causative agent of amebiasis, were found to have a decreased abundance of protective bacteria generally associated with gut health ( Verma et al, 2012 ). Cryptosporidium was found to alter microbiota composition in mouse models as well as in primates (Coquerel’s sifakas – Propithecus coquerel ), and dysbiosis was associated with enhanced parasite growth ( Ras et al, 2015 ; McKenney et al, 2017 ; Charania et al, 2020 ). Individuals infected with the protist Blastocystis show increased diversity of the gut microbiota in their fecal contents ( Audebert et al, 2016 ; Nieves-Ramirez et al, 2018 ).…”
Section: The Intestinal Microbiomementioning
confidence: 99%
“…Furthermore, loss of the microbiota in gnotobiotic and antibiotic-treated adult mice results in an increased susceptibility to Cryptosporidium infection ( 17 ), indicating that a diverse, mature microbiota provides a protective effect against Cryptosporidium sp. A recent study comparing different antibiotics revealed that cloxacillin treatment of mice induced changes in the microbiota and altered metabolites with increased susceptibility ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous work found that antibiotics alone did not sensitize immunocompetent mice to infection [25], although certain probiotics [71], antibiotics [72], and deprivation of prebiotics [73] could exacerbate disease severity.…”
Section: Discussionmentioning
confidence: 99%